2012
DOI: 10.1002/adma.201201273
|View full text |Cite
|
Sign up to set email alerts
|

Carbon‐Nanotube/Silver Networks in Nitrile Butadiene Rubber for Highly Conductive Flexible Adhesives

Abstract: An adhesive with high conductivity, flexibility, cyclability, oxidation resistance, and good adhesion is developed using microscale silver flakes, multiwalled carbon nanotubes decorated with nanoscale silver particles, and nitrile butadiene rubber. Light-emitting-diode chips are attached to the conductive, flexible adhesive pattern on a poly(ethylene terephthalate) substrate as a visual demonstration. The brightness is invariant during bending tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
107
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 27 publications
1
107
0
Order By: Relevance
“…Electrically conductive elastic nanocomposites with excellent abrasive resistance, high elasticity and good tightness have been widely used in various fields including sealing [1], electrostatic paints [2], electromagnetic shielding [3], stretchable electronics [4], flexible displays [5], smart skin [6], and implantable devices [7]. With low density, good chemical resistance, excellent electrical property, carbon-based fillers, such as carbon blacks [8], carbon fibers [9], carbon nanotubes (CNTs) [10] and graphene [11], have been introduced into elastomers (or rubbers) to take the advantages of the synergetic effect from the conductive carbon fillers and elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…Electrically conductive elastic nanocomposites with excellent abrasive resistance, high elasticity and good tightness have been widely used in various fields including sealing [1], electrostatic paints [2], electromagnetic shielding [3], stretchable electronics [4], flexible displays [5], smart skin [6], and implantable devices [7]. With low density, good chemical resistance, excellent electrical property, carbon-based fillers, such as carbon blacks [8], carbon fibers [9], carbon nanotubes (CNTs) [10] and graphene [11], have been introduced into elastomers (or rubbers) to take the advantages of the synergetic effect from the conductive carbon fillers and elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…15 Ma et al reported highly conductive exible adhesives (CFAs) composed of nanoscale Ag akes, CNTs and nitrile butadiene rubber. 16 Pillai et al reported a conductive hybrid network consisted of silver nanowires (Ag NWs) and SWCNT, which has been demonstrated potential in high energy density exible-solid-state supercapacitor. 17 Dong et al fabricated the Ag/CNTs networks for a highly conductive lm.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] The first strategy is the inclusion of micro-or nano-scale conductive carbon materials into elastic polymer matrices. 1,[10][11][12][13] For example, carbon-based materials, such as carbon nanotubes and graphene, have been extensively researched for stretchable/foldable conductors. Ma et al 13 fabricated helical ribbon-structured composites composed of carbon nanotubes and Ag flakes using a shape-memory polymer, demonstrating stable resistivity up to a strain of 600%.…”
Section: Introductionmentioning
confidence: 99%
“…1,[10][11][12][13] For example, carbon-based materials, such as carbon nanotubes and graphene, have been extensively researched for stretchable/foldable conductors. Ma et al 13 fabricated helical ribbon-structured composites composed of carbon nanotubes and Ag flakes using a shape-memory polymer, demonstrating stable resistivity up to a strain of 600%. However, the application of these materials in large-area, integrated devices may be restricted by their relatively poor electrical properties and their high cost.…”
Section: Introductionmentioning
confidence: 99%